Effectiveness of fiberglass glass bur, ultrasonic and manual mechanotherapy on grade II furcation involved mandibular molars (An in vivo comparative study) (Mustansiria Dental Journal, 2019)
Background: Access to the molars furcation areas is especially difficult for the patient and clinician alike due to the posterior location of molars, the dimension and position of furcation entrances, and the internal furcation surfaces that are frequently concave or irregularly contoured. The disparity between the size of commonly used scaling instruments and the size of the furcation entrance further complicates the situation.Materials and Methods: Thirty grade II furcation involved first and second mandibular molar  teeth from seventeen  patients. The clinical parameters that were measured included, Plaque index PI, Gingival index GI, Bleeding on probing BOP, Probing pocket depth PPD and Relative attachment level RAL. The furcation involved teeth included in the study were allocated in 3 groups according to the type mechanical treatment used. GROUP A (GA) :10 teeth treated by hand instrumentation by gracey curette. GROUP B (GB): 10 teeth treated by fiberglass rotary burs. GROUP C (GC)  : 10 teeth treated by ultrasonic scaler with special furcation tip. The clinical parameters were recorded at day (0) (baseline visit,) prior to surgical operations and repeated at (4 weeks), and (12 weeks) after operations. Results:  GROUP A, GB, and GC at (12 weeks) were respectively as the following: PLI (1.28,  1.03  and  0.56), GI (0.97,  1.12 and  0.60), BOP (37.88 %,  39.44 % and  11.66 %), PPD (3.11 mm, 2.8 mm and 1.28 mm) and RAL (3.36 mm,  3.47 mm and 2.7 mm). Conclusions: GROUP C Ultrasonic scaler revealed the highly significant reduction in the clinical parameters.  Followed by fiberglass burs and lastly by the curette. Also the three groups showed a highly significant reduction in all parameters as the time interval progressed (4 weeks), and (12 weeks).